Integrating information management for Microsoft Works and Works for Windows - Fairhurst, Maureen. (Nelson, 1993)
Information needs and integrated systems. Business spreadsheets. Business databases. Manipulating data in a database. Moving and integrating data. Business graphics. Word processing and mail merge. Accessories and options. Developing an integrated business information system. Communications